Overcoming Penal Boundaries: Exploring The Evolution of Retributive Time Through Parole Decision-Making. (3rd May 2021) - Dagan, Netanel
Abstract: The relations between sentencing and post-sentencing stages (e.g., the implementation of prison, parole or community-based sanctions) are often perceived through temporal, spatial and normative binaries. The static time of retributive calibration—as fully known at sentencing time—stands at the heart of this separation. Through qualitative findings drawn from parole-board chairpersons in Israel, the paper argues that retributive punishment may evolve with time. As the findings suggest, parole decision-makers often go beyond risk and rehabilitation and reframe, reinterpret and renegotiate the dimensions of the deserved punishment. Three temporally dynamic themes of retributive discourses were described: (1) unexpected suffering review; (2) moral character revaluation; and (3) diminished censure reassessment. The findings challenge both the static conceptualization of retributive time and the instrumental view of parole decision-making. More generally, the findings question the assumed strict boundaries between sentencing and post-sentencing stages and call for future scholarly engagement with the evolution of punishment over time.